Neurodegeneration in Patients with Type 2 Diabetes Mellitus without Diabetic Retinopathy - Elena Garcia-Martin; Marta Cipres; Isabel Melchor; Laura Gil-Arribas; Elisa Vilades; Vicente Polo; Maria Jesus Rodrigo; Maria Satue (Journal of Ophthalmology)
Purpose. To evaluate neurodegeneration in patients with type 2 diabetes mellitus (DM2) without diabetic retinopathy and to assess the possible role of systemic vascular complications in retinal changes. Methods. Sixty eyes of 60 patients with DM2 and without any signs of diabetic retinopathy and 60 eyes of 60 healthy controls underwent retinal evaluation using Spectralis optical coherence tomography. Macular ganglion cell layer (GCL) and retinal nerve fiber layer (RNFL) were evaluated. Peripapillary RNFL thickness was assessed using Glaucoma and Axonal Analytics applications. Comparison between patients with the presence/absence of systemic vascular complications and different disease duration was made. Results. Macular GCL was reduced in patients compared to controls (p<0.001). Differences in the macular RNFL thickness were only observed in the outer inferior sector (p=0.033). A reduction in the peripapillary RNFL (average, inferior, and inferotemporal thickness, p<0.05 for all three) was observed in patients using both applications. Patients with chronic systemic vascular complications presented a reduction in the temporal RNFL (p=0.019) compared to patients without complications. The superotemporal RNFL thickness was thinner in patients with longer disease duration. Conclusions. Patients with type 2 DM without diabetic retinopathy and good metabolic control present neurodegeneration affecting neurons in the macular area and axons in different sectors of the optic disc. Systemic vascular complications contributed to further axonal damage in these patients, suggesting a possible role of subclinical ischaemia to retinal neurodegeneration in type 2 DM.